On the Influence of Microtopography on the Sliding Performance of Cross Country Skis - Scherge, Matthias; Stoll, Melissa; Moseler, Michael (Frontiers in Mechanical Engineering, 2021)
The sliding performance of cross country skis is mainly influenced by the ability of the ski base to minimize capillary forces and contact area. Whereas the first condition depends on hydrophobicity, the second one is controlled by the ski grinding structure and the morphology of snow. In this contribution the results of sliding tests with 5 typical grinding structures will be presented and compared to calculations of the real area of contact. Surface topographies were measured and corresponding roughness features were analyzed by 3D optical microscopy. The measured ski base profiles and the measured grain size distribution of granular snow at -2°C were employed within a bearing model for a rough surface in contact with loose and freely-moving snow grains treated as ice spheres. For the 5 grinding structures, this model revealed a good correlation of the real area of contact between ski and snow with run times in lab-condition sliding tests. The results indicate that the snow-containing volume of the grinding structure is pivotal for tailoring the sliding behavior.